2014
DOI: 10.1021/ml500240d
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 2-Pyridylpyrimidines as the First Orally Bioavailable GPR39 Agonists

Abstract: The identification of highly potent and orally bioavailable GPR39 agonists is reported. Compound 1, found in a phenotypic screening campaign, was transformed into compound 2 with good activity on both the rat and human GPR39 receptor. This compound was further optimized to improve ligand efficiency and pharmacokinetic properties to yield GPR39 agonists for the potential oral treatment of type 2 diabetes. Thus, compound 3 is the first potent GPR39 agonist (EC 50 s ≤ 1 nM for human and rat receptor) that is oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 20 publications
(31 reference statements)
5
47
0
Order By: Relevance
“…5). This is in agreement with a previous study (Peukert et al, 2014), which showed an EC 50 value of 60 nM and an efficacy of 64% of the activity shown by 25 mM forskolin. Another study found that the GPR39 agonists AZ1395, 3,4-bis-(2-imidazol-1-ylethoxy)-benzonitrile; AZ4237, 6-[(4-chlorophenyl)methyl]-7-hydroxy-5-methyl-pyrazolo[1,5-a]pyrimidine-3-carboxylic acid; AZ7914, 6-(3-chloro-2-fluoro-benzoyl)-2-(2-methylthiazol-4-yl) -3,5,7,8-tetrahydropyrido-[4,3-d]pyrimidin-4-one also stimulated cAMP responses without Zn 21 (Fjellström et al, 2015); however, the phosphodiesterase inhibitor 3-isobutyl-1-methylxanthine (IBMX) was used in that study, which makes estimation of the "true" pharmacological parameters of these compounds difficult.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…5). This is in agreement with a previous study (Peukert et al, 2014), which showed an EC 50 value of 60 nM and an efficacy of 64% of the activity shown by 25 mM forskolin. Another study found that the GPR39 agonists AZ1395, 3,4-bis-(2-imidazol-1-ylethoxy)-benzonitrile; AZ4237, 6-[(4-chlorophenyl)methyl]-7-hydroxy-5-methyl-pyrazolo[1,5-a]pyrimidine-3-carboxylic acid; AZ7914, 6-(3-chloro-2-fluoro-benzoyl)-2-(2-methylthiazol-4-yl) -3,5,7,8-tetrahydropyrido-[4,3-d]pyrimidin-4-one also stimulated cAMP responses without Zn 21 (Fjellström et al, 2015); however, the phosphodiesterase inhibitor 3-isobutyl-1-methylxanthine (IBMX) was used in that study, which makes estimation of the "true" pharmacological parameters of these compounds difficult.…”
Section: Discussionsupporting
confidence: 94%
“…The structures of these compounds are similar to each other, but are markedly different from the GPR39-C3 compound that has previously been reported to be an agonist at GPR39 ( Fig. 1B; Peukert et al, 2014). When tested at 11 other GPCRs, neither of these compounds showed agonist activity (Fig.…”
Section: Resultsmentioning
confidence: 43%
See 2 more Smart Citations
“…GPR39 is a conserved orphan GPCR that has been shown to be involved in zinc ion transport as well as other aspects of metabolic regulation [8]. Recently, a new compound named TC-G 1008 (also named as GPR39-C3) was developed based on 2-pyridylpyrimidines and has been shown to be highly specific in binding to GPR39, making it a powerful tool to investigate the function of this receptor in diverse cell types [9,10]. GPR39 has been shown to be expressed in different osteoblast cell lines [11].…”
Section: Gpr39 Agonist Tc-g 1008 Promotes Osteoblast Differentiationmentioning
confidence: 99%